2014
DOI: 10.1007/s11912-014-0419-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiotherapy for Gastrointestinal Malignancies: Contemporary Outcomes With Multimodality Therapy

Abstract: The integration of intraoperative radiotherapy (IORT) into the multimodal treatment of gastrointestinal cancer is feasible and leads to high rates of local control. In-field tumoral control using IORT-containing strategies can be achieved in over 90 % of most cases, regardless of the site or status of the tumor (primary or recurrent). Electron beam IORT, or intraoperative electron radiation therapy, is the dominant technology used in institutions reporting data in publications the 21st century. Neither surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In a phase three clinical trial [10], the rate of ipsilateral breast tumor recurrence in the IOERT group was higher than in the external irradiation group, the overall survival rate did not differ between the two groups. However, in another phase three clinical trial, IOERT showed no advantage in local control and survival over surgery alone, but the security and reliability of IORET were confirmed [8]. For children with soft tissue sarcoma, IOERT can bring better local control with fewer adverse reactions at a lower dose than external radiation [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase three clinical trial [10], the rate of ipsilateral breast tumor recurrence in the IOERT group was higher than in the external irradiation group, the overall survival rate did not differ between the two groups. However, in another phase three clinical trial, IOERT showed no advantage in local control and survival over surgery alone, but the security and reliability of IORET were confirmed [8]. For children with soft tissue sarcoma, IOERT can bring better local control with fewer adverse reactions at a lower dose than external radiation [12].…”
Section: Discussionmentioning
confidence: 99%
“…IORET also improves the control and survival rates for skull base tumors [13], and improves local control in advanced cervical cancer [14]. Calvo et al [8] reviewed the use of IOERT for gastrointestinal tumors, and suggested that IOERT improves local control of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%